Halal Haram Cryptocurrency - Idrus (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2021)
The invention of the computer which was originally a calculating machine (Difference Engine no. 1) which was discovered by Charles Babbage (1791-1871) is something very famous in the history of computer development and is the first automatic calculator. With the very rapid development of the digital world, in 1983 an American cryptography expert David Chaum used cryptographic electronic money called e-cash, and in 1995, he implemented it through Digichash, which became the initial form of collaboration between the digital world of computers and Money, which is a cryptographic electronic payment instrument that requires user software to pull notes from the bank and designate a specific encrypted key before it can be sent to the recipient. And in 1996, the NSA, namely the United States National Security Agency, which was founded by President Harry S. Truman on November 4, 1952, had the task and function of collecting and analyzing communications from other countries, as well as protecting information belonging to the United States. The agency published a paper entitled How to Make a Mint: The Cryptography of Anonymous Electronic Cash, describing the Crypto currency system that first published it on the MIT mailing list, later in 1997, in the journal The American Law Review (Vol. 46, Issue 4). It was these researches that eventually led the developers to start developing what is known today as blockchain which is basically a distributed open ledger to record transactions between two parties efficiently and in a verifiable and permanent way. The discovery of Bit coin in 2009 which was declared as electronic money was developed by an institution or individual who has the initials Satoshi Nakamoto, the technology used is using a peer to peer network without centralized storage so that verification can be done anywhere in the world anywhere that dedicates a computer, to do this or it is called mining. Since 2009 other coins and tokens have started to appear, as we can see on CoinMarketcap which has more than 6000 coins and tokens. The utilization and use of this technology is still being debated from the point of view of Muslims in Indonesia, as stated by Yenny Wahid in the activities carried out by the Islamic Law Firm (ILF), this is due to the uncertainty of the asset value which can change at any time.